Dilema Digitalisasi Pasar Tradisional: Perspektif Pedagang Pasar Senen Jakarta - Dewa Putu Yohanes Agata L. Sandopart (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study explores the digitalization dilemma of traditional markets from the perspective of Pasar Senen Jakarta traders. Amid national policy accelerating payment digitalization through QRIS (Quick Response Code Indonesian Standard), traditional market traders face structural contradictions between the demands of technological adaptation and the sustainability of value-based traditional livelihoods. Using a qualitative approach with a single case study design, this study involved 17 purposively selected participants. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using a six-phase thematic analysis. The study found four main themes, including tension between efficiency and income uncertainty, payment system dualism as a survival strategy, digital literacy barriers and generational gaps, and social capital dynamics in digital adaptation. The novelty lies in revealing systemic betrayal in digitalization, where infrastructure designed for inclusion produces new forms of exclusion. Trader resistance is not merely a result of technological conservatism but a rational response to the uncertainty produced by the system itself. This study contributes to the development of innovation resistance theory and provides policy implications for more inclusive digitalization that prioritizes the interests of small-scale traders.